The impact of COVID-19 pandemic on students’ learning in higher education in Afghanistan - Abdul Qawi Noori (Heliyon, 2021)
COVID-19 pandemic has been a global serious issue that adversely impacted humans' life. This study aimed to investigate the impact of the COVID-19 pandemic on students' learning in higher education in Afghanistan. A mixed method research design was employed in conducting the study. The quantitative data were gathered using an online survey questionnaire from 592 randomly selected students and 6 semi-structured interviews were conducted to collect qualitative data. Statistical Package for Social Sciences (SPSS) was used to analyse the quantitative data and the qualitative data were coded and analysed thematically. The quantitative finding showed that the students did not experience a constant online teaching and learning during the COVID-19 pandemic. It also revealed that the COVID-19 pandemic devastatingly affected students’ learning in higher education in Afghanistan. In addition, the qualitative finding revealed that the students had problems with Internet and technological facilities in their learning and they suggested that the Ministry of Higher Education should design and introduce a practical online platform which will be free and accessible with a poor Internet connection because some of the students live in areas where the Internet speed is very slow. The finding of the study will help educational managers and higher education leaders to review and adopt policies for teaching and learning in emergency cases. It will also help lecturers to design a proper plan and improve their instruction.